Konsep Bisnis Pemasaran Produk Minuman Sarang Burung Walet Fit With Realfood di PT Realfood Karya Indonesia - Ramadhanti, Azahra Putri; Djuwendah, Endah; Budiman, Muhammad Arief; Qanti, Sara Ratna (Universitas Galuh, 2025)
The population of edible bird's nests in Indonesia accounts for 80-85% of the world's total, making Indonesia the leading producer of edible bird's nests. One of the companies that produces processed bird's nest drinks is Realfood. This company is the first pioneer of bird's nest drinks in Indonesia. With its flagship product, Fit With Realfood, the company's presence was well-received, especially during the Covid-19 pandemic. However, over the past two years, Realfood has experienced a decline in sales. The purpose of this study is to understand the business concept of PT Realfood Karya Indonesia in marketing its products. The study employs a qualitative research design with a case study approach. Data collection methods include observation, interviews, and documentation, while data analysis is conducted using descriptive analysis and the business model canvas tool. PT Realfood Karya Indonesia's business concept follows the unbundling business model approach. Product marketing is the primary focus of PT Realfood Karya Indonesia. Consequently, the resulting business model canvas highlights the company's efforts to generate revenue through product marketing